1999
DOI: 10.1038/sj.bjc.6690682
|View full text |Cite
|
Sign up to set email alerts
|

Familial adenomatous polyposis is associated with a marked decrease in alkaline sphingomyelinase activity: A key factor to the unrestrained cell proliferation?

Abstract: SummaryThe hydrolysis of sphingomyelin generates key molecules regulating cell growth and inducing apoptosis. Data from animal cancer models support an inhibitory role for this pathway in the malignant transformation of the colonic mucosa. In the intestinal tract, a sphingomyelinase with an optimum alkaline pH has been identified. We recently found that the activity of alkaline sphingomyelinase is significantly decreased in colorectal adenocarcinomas, indicating a potential anticarcinogenic role of this enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 25 publications
5
53
1
Order By: Relevance
“…Second, the enzyme inhibits proliferation of human colon cancer cells (Hertervig et al, 2003). Third, the enzyme activity is reduced in both longstanding ulcerative colitis and colonic tumorigenesis (Hertervig et al, 1997(Hertervig et al, , 1999Sjöqvist et al, 2002). And finally, mutation has been identified in colon cancer cells, which abolishes the enzyme activity (Wu et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the enzyme inhibits proliferation of human colon cancer cells (Hertervig et al, 2003). Third, the enzyme activity is reduced in both longstanding ulcerative colitis and colonic tumorigenesis (Hertervig et al, 1997(Hertervig et al, , 1999Sjöqvist et al, 2002). And finally, mutation has been identified in colon cancer cells, which abolishes the enzyme activity (Wu et al, 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it degrades lysophosphatidylcholine by a phospholipase C activity, thus reducing the formation of lysophosphatidic acid, a potent factor that stimulates cell migration and angiogenesis (Duan, 2006;Wu et al, 2006). We previously found that alk-SMase activity was decreased in colonic adenomas and carcinomas, in familial adenomatous polyposis and in longstanding ulcerative colitis (Hertervig et al, 1997(Hertervig et al, , 1999Sjöqvist et al, 2002). The reduction was recently confirmed and the levels of alk-SMase in the faeces have been considered as a potential marker for diagnosis and prognosis of colon cancer (Di Marzio et al, 2005).…”
mentioning
confidence: 99%
“…Theoretically, this could be due to decreased colonic expression, and/or secondary to decreased release of the enzyme in the small intestine, as Alk-SMase is extremely resistant to the pancreatic proteases present in the gut lumen and faeces [15]. The activity in the colon may contribute to colonic generation of sphingolipid metabolites that have been ascribed an antitumour effect [9,33,34]. By inference, the reduced Alk-SMase in the colon by bile diversion may be of interest to further delineate its potential implications in colonic tumorigenesis or tumour promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary supplement with SM and ceramide analogues was found to inhibit development of chemically induced colon cancer in animal studies (12)(13)(14). We previously found that alk-SMase activity was significantly reduced in the tissues of human colon adenomas and carcinomas (15,16) and in the mucosa of longstanding ulcerative colitis (17), indicating that the reduced SM hydrolysis in the gut may increase the susceptibility of the colonic mucosa to carcinogenic factors. SM metabolism in the gut may also affect cholesterol absorption, because both dietary SM in the gut (18, 19) and hydrolysis of SM in the membrane of enterocytes by SMase (20) were found to inhibit cholesterol absorption.…”
mentioning
confidence: 99%